IMPROVING THE EIGHT GRADE STUDENTS’ READING COMPREHENSION OF FABLE TROUGH QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY AT SMP TUNAS PELITA BINJAI - Ade Wahyuni Azhar; Resty Tarigan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Reading comprehension is a process to recognize the text and remember any information in the text. The preliminary observation found that the students in Junior High School had problem in reading comprehension. The students were difficult to find general informatioin, specific information, textual meaning and recognize textual reference in the reading text. Classroom Action Research dealt with improving reading comprehension through Question Answer Relationship strategy of the Eight Grade studenta of SMP Tunas Pelita Binjai that consised of 20 students. This research was conducted in two cycles. The data were analyzed by comparing the resulit of pre-test and post-test in cycle 1 and cycle 2 that were given to ethe subjects. Based on the data analysis,it was found that the students’ score improved. In the Pre-test, the mean of the students’ score is 56,25 and the number of students about 75 (KKM) is 7 students. In cycle 1, the mean of the students’ score is 72,25 and the number of students about 75 (KKM) is 12 students. And the lst, in the cycle 2 the mean of the students’ score is 83,75 and the number of students about 75 (KKM) is 17 students. Based on the observation,sheet, it shows that the expression and excitement of the students were also improved. It suggested that an English teacher apply this strategy as one of the alternative in teaching reading comprehension. Keywords: Improving, Reading comprehension, fable, Question Answer Relationship (QAR) strategy.